Implementasi Metode Lancar Membaca & Menulis Indah (LMMI) Untuk Pengenalan Literasi - Idawati, Sulis; Astri Nurhidayati; Ariesta Luciana Hendrika; Sultiyah; Fathurrohman (STAI Al-Amin Gersik Kediri Lombok Barat NTB, 2024)
This research is based on the fact that the ability to read and write in early childhood is very important for their future development. And to prepare children to enter the next level. However, there are still obstacles in introducing literacy to young children. Therefore, it is important to look for methods that can help young children develop the ability to read and write fluently and effectively. The aim of this research is how to implement the fluent reading and writing beautifully (LMMI) literacy method in early childhood. And it is hoped that children can improve their reading and writing skills from an early age. Apart from that, this research also aims to determine the effectiveness of the (LMMI) method in developing literacy in early childhood. This research method uses descriptive qualitative methods. A qualitative approach is research that displays assessment procedures that produce descriptive data in the form of written or spoken words from people and observed behavior. In this case, the researcher interprets and explains the data obtained by the researcher from interviews, observations, documentation. The observation method is an investigation carried out deliberately systematically using the senses. Interviews are a way of collecting data by holding questions and answers with people who can provide information. The documentation method is a data collection technique by collecting and analyzing documents, both written, image and electronic documents. The results of this research are limited to the application of the (LMMI) method for fluent reading and writing beautifully and early literacy in early childhood. This research will involve teachers, parents and young children. This research will cover the implementation process and measure the effectiveness of this method in developing the reading and writing skills of young children. shows that by using the LMMI method children are more receptive and very effective in using it for literacy learning so that indicators of children understanding reading and writing and the goals that the teacher will achieve are achieved.